RELEVANSI MAT 28:19-20A BAGI PRAKTEK PEMBAPTISAN DAN PENGAJARAN GEREJA - F.X. Didik Bagiyowinadi (Litbang STFT Widya Sasana Malang, 2010)
In this article I study the Greek text of Matt. 28:19-20a and search its’ implication for the baptismal and catechetical practices of the Catholic Church. Among the four verbs in this text, the main verb is only the imperative “make the disciples”, the others are participle verbs. It means that the activity of “go” must be directed to “make the disciples” as the purpose. “Baptizing” and “teaching” are the means how this great command can be realized. In this text nothing mentions any instruction or condition before verb “baptizing”, so that the infants can be baptized, as soon as they become Christ’ disciples. The participle of “teaching” follows “baptizing”, it refer any catechetical formation after baptism, especially in the orthopraxis, how become Christ’ disciples. This process is never finished because we are always only the disciples of Christ (cf. Matt. 23:8)